Formalin infiltration of ductus arteriosus in cyanotic congenital heart disease. Issue 5 (May 1981) - Deanfield, J E; Rees, P G; Bull, C M; de Leval, M; Stark, J; Macartney, F J; Taylor, J F
Abstract : Formalin infiltration of the ductus arteriosus was performed in 13 neonates with pulmonary atresia (three with ventricular septal defect, two with tricuspid atresia, and eight with intact ventricular septum, one of whom had Ebstein's anomaly) in an attempt to maintain duct patency. Nine patients had an additional retrograde pulmonary valvotomy and one a Blalock-Taussig shunt. The mean preoperative systemic PO2 was 31 mmHg and rose significantly to 46 mmHg after operation. However, the PO2 rose in only two of the four patients who had formalin infiltration alone. There were five early deaths and three had clinical evidence of duct closure. Four patients needed further surgery (systemic-pulmonary artery shunt) within eight days. Seven of eight surviving patients were shown to have a closed duct at repeat cardiac catheterisation (two to 13 months after operation). The eighth died before restudy. There were four late deaths, one following late reoperation and the other three within five months of early reoperation. These results suggest that formalin infiltration cannot ensure long-term duct patency. As short-term patency can be maintained more reliably by prostaglandin administration, we have abandoned the operation.